Effects of summer peaks on brown trout and Atlantic salmon growth and survival in hydropower-regulated Gullspång River - Hallberg, Oscar (Karlstads universitet, Fakulteten för hälsa, natur- och teknikvetenskap (from 2013), 2023)
Daily demands for electrical power are met through sub-daily release of turbined water in the form of hydropeaking. Hydropeaking’s changes to stream flow are listed as a threat to biodiversity in river ecosystems as it causes rapid habitat alteration such as increased depth and velocity, affecting the species living downstream. The brown trout and landlocked salmon populations in Gullspång River, Sweden, are threatened and subjects to the hydropeaking regime. This study investigated the effects of hydropeaking in summertime (summer peaks) in Gullspång River on growth and survival of age 0 (fry) and age 1 (parr) brown trout and Atlantic salmon. The study used an individual-based model (inSTREAM 7.2-SD) to predict how different peak scenarios would affect the different species and age groups. A previous study’s parameters and model calibration for the study area were used, and I manipulated the flow time-series to create new flow time-series including three single peaking scenarios on different dates during summer, one multiple summer peak scenario as well as a no-peak (steady flow) scenario. The analysis focused on qualitative patterns in how the populations responded to the various flow scenarios. Age 0 salmon’s growth and survival were negatively affected by all peaking scenarios in comparison to the steady flow scenario, with the combined peaking scenario having the worst effect. Age 0 trout survival was either unaffected by single peaking (Scenario 1 & 2) or negatively affected (Scenario 3) and was also worst affected by the combined peaks compared to steady flow. Age 1 survival of both species was positively affected by the combined peaking but either unaffected (Scenario 1 & 2) or negatively (Scenario 3) affected by single peaks compared to the steady flow scenario. Age 1 growth followed a similar trend with highest growth rate in the combined peaks scenario and the lowest in the steady flow for both species. Results of the study may contribute to river management decisions regarding choice of ...